(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of the application of the case study method on the news text writing skills of grade XI students of SMA Negeri 2 Tambang. This research is motivated by the importance of writing skills as one of the language competencies that play a role in developing students’ critical, analytical, and creative thinking skills. However, students’ ability to write news texts is still relatively low, especially in compiling information systematically, factually, and according to the rules of news writing. This study uses a quantitative approach with experimental design. The research subjects consisted of grade XI students who were divided into two groups, namely the experimental class and the control class. The data collection technique was carried out through a news text writing skill test given before (pretest) and after (posttest) treatment. The data obtained was analyzed using statistical tests to determine the difference in learning outcomes between the two groups. The results of the study showed that the application of the case study method had a significant effect on improving students’ news text writing skills. This can be seen from the increase in the average score of students in the experimental class which is higher than the control class. The case study method encourages students to analyze events, identify facts, and organize information into more structured and informative news texts.